8th International Workshop and conference of the International Society of Performance Analysis of Sport, 11th-13th of September 2019 (Budapest, Hungary) "Technology meets Practice and Science". Programme Abstracts (2019)
Main topics: Performance Analysis, Data Analytics, Technology in Sport Coaching "Technology meets Practice and Science"